The Implementation of Human Resource Management in Improving School Effectiveness (Universitas Pamulang, 2025)
This study aims to examine how human resource management (HRM) deployment can enhance school efficacy. The caliber of current human resources, such as teachers, administrative personnel, and management, has a significant impact on how effective schools are in the educational context. The caliber of these human resources is crucial to fostering a positive learning environment and assisting students in achieving their academic objectives. A case study was used in this study. methodology in conjunction with a qualitative approach in a number of urban and rural schools. In-depth interviews with principals, educators, and administrative personnel were used to gather data, in addition to firsthand observation of the HRM procedures that were put into place. According to the study's findings, implementing sound HRM procedures—like performance reviews, continuous training, and selective hiring—significantly increases the efficacy of educational institutions. While continuous training aids in teachers' skill and knowledge development, selective recruitment guarantees that only competent people join the teaching staff. Constructive performance review also motivates teachers to keep refining their instructional strategies. The significance of HRM in developing successful and high-quality schools is thus supported by this study